Flipbook-Based Project-Based Learning: An Opportunity to Improve Science Literacy - Henzi Haryanto; Hayuni Retno Widarti; Aynin Mashfufah; Radeni Sukma Indra Dewi; Shirly Rizki Kusumaningrum (Postgraduate, University of Mataram, 2024)
Problems that often occur in schools are the use of learning media. Moreover, learning media can make students feel happy. So that the desired abilities can be achieved, such as science literacy. Science literacy is an ability that needs to be improved starting from elementary school. This aims to make students able to later compete in the community environment. This research uses a qualitative descriptive method. This method can be the first step to describe or analyze the problems that occur in the field and will later be developed further. The sources obtained in this study came from interviews with teachers and questionnaires on the favourability of using learning media for students. The result is that students like learning that involves them in learning, coupled with using media that can be seen and heard such as YouTube or multimedia learning. However, many teachers still have difficulty in applying interactive media. The use of flipbooks can be a solution for teachers, considering that teachers have many learning accounts that have access to the use of applications to create flipbooks, such as CanvaPro. This flipbook-based learning media itself is able to make students think creatively and improve science literacy by combining project-based learning (PJBL).